FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN INFEKSI SALURAN PERNAPASAN ATAS PADA BALITA PUSKESMAS UJUNG BATU KABUPATEN ROKAN HULU - Ramadho, Ari Rizky; Sutomo, Sumengan; Harnani, Yessy; Rahayu, Endang Purnawati; Susmaneli, Herlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Up Respiratory Infection (URI) is one of the leading causes of death in children under five years of age in the world. The incidence of ARI in Rokan Hulu Regency is in the first place with the number of 4118 cases in the 2019 period. The highest ARI cases were found in Ujung Batu Health Center, Rokan Hulu Regency, compared to Puskesmas Kunto the incidence of ISPA reached 211 cases. The research objective was to determine the factors that influence the incidence of upper respiratory tract infections at the Ujung Batu Health Center, Rokan Hulu Regency. The research method used quantitative type and cross sectional design. The population in this study were all households in the Ujung Batu Health Center, with a sample of 157 people. The sampling technique used simple random sampling. Using primary data, with observation sheet instruments and questionnaires. Data analysis used univariate, bivariate and multivariate analysis. The results showed that there was an effect of the wall effect on the incidence of ARI (pvalue = 0.017), and there was an effect of ventilation with the incidence of ARI (pvalue = 0.000 <0.05). In addition, there is no effect of road facilities, cooking fuel and house floors with the incidence of ARI at the Ujung Batu Health Center, Rokan Hulu Regency. It is hoped that the puskesmas will be able to enter with the local community in disseminating the conditions for a healthy house on a regular basis, improving the condition of the walls and ventilation of the house which are still not in accordance with the standards of a healthy house. Bibliography: 35 References (2009-2015)Keywords: Up Respiratory Infection, factors